Optimal Combination of Traditional and Innovative Means of Protecting Notarial Information - Ilyosbek, Odilhujaev (Law and Justice, 2024)
The protection of sensitive notarial information requires optimally integrating traditional and innovative security techniques. This paper analyzes the strengths and weaknesses of established methods like paper documents and seals alongside emerging solutions like encryption and blockchain for safeguarding data. A comparative framework evaluates approaches across dimensions of cost, usability, resilience and compliance. Recommendations are provided for layered security combining physical and digital methods to holistically address evolving threats. The analysis finds that synergistically blending time-tested and novel tools can enhance notarial information protection.